HUBUNGAN PANJANG BERAT IKAN LAYANG ( DECAPTERUS SP.) YANG TERTANGKAP DI PERAIRAN ACEH UTARA YANG DIDARATKAN DI PELABUHAN PERIKANAN SAMUDERA (PPS) LAMPULO ACEH UTARA - Mila Sianipar; Lidia Samosir; Grace Purba; Erwin Sapeai; Wendy Pakpahan; Ria Retno (Journal of Research and Publication Innovation, 2024)
Aceh waters are a place for fishermen to look for fish, one of which was flying fish (Decapratus sp.) which was landed at the Lampulo Ocean Fisheries Port (PPS), North Aceh. Flying fish (Decapratus sp.) was a fishery commodity that was in great demand by people globally, especially in Indonesia. This research aims to measure the length and weight of flying fish (Decapratus sp.) using survey and analysis methods. The results of this research obtained a value for the total number of fish which was 50 fish. With the overall sample length of fish ranging from 140 mm to 205 mm, the dominant total length of fish caught was in the average range of 166.28 mm. Meanwhile, the weight of flying fish (Decapterus sp.) ranges from 31 to 76 grams, with an average fish weight of 46.06 grams. The calculation result of the b value obtained from testing the flying fish (Decapterus sp.) at the Pematangsiantar Parbesaran Market was 2.68, with the r2 value being 0.89. Based on the b value obtained, it can be stated that the length and weight of the fish was < 3, which means negative allometric meaning that length growth is faster than weight growth.